Synchronous Generator Imitation Control and Dynamic Power Sharing for Distributed Power Generation Systems - Xiao, Huangqing; Liu, Bicheng; Huang, Xiaowei; Cai, Zexiang (Frontiers in Energy Research, 2022)
In this paper, a control method called synchronous generator imitation control (SGIC) as well as a dynamic power sharing for distributed power generation systems (DPGSs) are presented. In order to imitate the behavior of a synchronous generator (SG), the SGIC method for the voltage source converter (VSC) station is proposed. The SGIC includes three loops, namely active power and frequency loop (Pf loop), reactive power and voltage loop (QU loop) as well as inner current loop. The Pf loop is used to emulate the swing equation of the SG. The exciter of the SG is mimicked by the QU loop. The inner current loop is developed for fast current and voltage regulations as well as current limiting. The system stability performances are analyzed through small-signal model, and the effectiveness of the proposed control is validated by PSCAD/EMTDC simulations. The results show that the Pf loop of the VSC emulates the motion equation of the SG rotor very well, which makes the VSC station to have inertia just as a SG; the VSC station can maintain a stable output voltage and regulate the reactive power at the same time; through the dynamic power sharing, precise power control, frequency offset elimination and system stability improvement are achieved; the system has the merits of fault ride-through capability as well as good dynamic performance.